Equations and Stable Modes of Parametron - Privalova, O.V.; Shtukin, L.V.; Skubov, D.Yu. (Journal of Applied Nonlinear Dynamics, 2026)
This work is devoted to investigation of nonlinear electric circuit—the resonance scheme with nonlinear reactive element. The role of this non-linearity plays the saturation of magnetic transformed coupling. The stationary mode in this scheme is supported by generator of alternating current. The idea of work of parametron is an opportunity of two stationary modes of current corresponded to borders of the main zone of parametrical resonance. These modes are used as binary logical states with high-frequency ability of switching. The efficiency of this scheme increases with growth of frequency and simultaneously decreasing of scale. The aim of this article is a summarizing of the method of study for scheme of this type for this and some analogous devices.